2017
DOI: 10.1002/maco.201609415
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term polarisation and immersion for copper corrosion in high‐level nuclear waste environment

Abstract: Long‐term polarisation and immersion for copper corrosion were investigated in chloride‐containing sulphide solutions. Results showed that no active state exists for copper in sulphide‐containing solutions, whereas a typical active‐to‐passive transition exists in the second passivation region, indicating a hydroxyl activation effect on copper. After the sulphide passive film broke down, the pitting area was re‐passivated by hydroxide ions; however, if the chloride and sulphide concentrations were both high, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
(22 reference statements)
3
9
1
Order By: Relevance
“…These observations, however, conflict with claims, [16][17][18] based on EIS measurements and Mott-Schottky analyses, that film growth was controlled by the transport of Cu + vacancies within a passive film, with a diffusion coefficient in the range of 10 −14 to 10 −15 cm 2 /s. These values, obtained for films ranging from ∼0.1 μm to ∼50 μm in thickness, are considerably lower than the diffusion coefficients measured for Cu + vacancies in various copper sulfides, which vary with the degree of non-stoichiometry, decreasing from ∼10 −8 cm 2 /s for chalcocite (Cu 2 S) to 10 −9 cm 2 /s for djurleite (Cu 1.96 S), to 10 −10 to 10 −11 cm 2 /s for anilite (Cu 1.75 S) and 10 −12 cm 2 /s for covellite (CuS).…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…These observations, however, conflict with claims, [16][17][18] based on EIS measurements and Mott-Schottky analyses, that film growth was controlled by the transport of Cu + vacancies within a passive film, with a diffusion coefficient in the range of 10 −14 to 10 −15 cm 2 /s. These values, obtained for films ranging from ∼0.1 μm to ∼50 μm in thickness, are considerably lower than the diffusion coefficients measured for Cu + vacancies in various copper sulfides, which vary with the degree of non-stoichiometry, decreasing from ∼10 −8 cm 2 /s for chalcocite (Cu 2 S) to 10 −9 cm 2 /s for djurleite (Cu 1.96 S), to 10 −10 to 10 −11 cm 2 /s for anilite (Cu 1.75 S) and 10 −12 cm 2 /s for covellite (CuS).…”
contrasting
confidence: 73%
“…Other authors have claimed that the film formed on Cu under electrochemical conditions in 2 × 10 −4 M SH − was passive in nature, [16][17][18] which ultimately led to Cl − -induced breakdown and pitting at very positive potentials. However, these claims were based on polarization curves recorded under stagnant conditions, while our results, recorded at a rotating disk electrode (RDE), 7 demonstrated that the current observed was due to film growth partially controlled by SH − transport, a situation which precluded the possibility of passivation.…”
mentioning
confidence: 99%
“…Firstly, in the presence of sulphide, the corrosion potential, E corr , of the cast NAB moves forward in the negative direction and decreases with the increase of SC. This phenomenon is caused by the adsorption of HS − on the NAB surface [29,30], as also reported in other studies [13,29,30]. Secondly, both the anodic and cathodic branches of the polarisation curves change distinctly when the SC exceeds 50 ppm.…”
Section: Electrochemical Resultssupporting
confidence: 79%
“…Other cathodic reactions will proceed in the presence of sulphide. In the solutions with SC higher than 50 ppm, the E corr decreases to approximately − 1.0 V. The cathodic branch of the polarisation curve indicates the occurrence of a charge transfer-controlled process, which corresponds to the following hydrogen evolution reaction [11,29,30]:…”
Section: Electrochemical Resultsmentioning
confidence: 99%
“…Pitting is a common form of localized corrosion, and a major concern due to its unpredictability, ability to penetrate the bulk material, and self-sustaining nature. Many studies have been conducted on the properties of passive films, such as their structure, composition, and thickness and their role in pitting 4,8,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] .…”
Section: Introductionmentioning
confidence: 99%